2016
DOI: 10.4209/aaqr.2015.09.0533
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Health Risk of Carbonyl Compounds in Air of the Library in Guangzhou, South China

Abstract: The concentrations of 18 carbonyl compounds and their health risks for people were investigated in indoor and outdoor air of three different rooms of a library in Guangzhou, South China. Indoor air samples were collected during normal activities of staff and students, and carbonyl compounds were analyzed by high-performance liquid chromatography. The results show that the total concentrations of 18 carbonyls ranged from 8.8 to 73.9 µg m -3 with a mean value of 24.7 µg m -3. Acetone was the most abundant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…These two species have been targeted in numerous toxicological studies owing to their deleterious health effects (Health and Services, 1999; Neghab et al, 2017; Salthammer et al, 2010; Til et al, 1988; Tunsaringkarn et al, 2012b, 2012c). Their ubiquity and importance in ambient air have been documented in many past studies (Lü et al, 2016; Neghab et al, 2017; Sarkar et al, 2017). Owing to rapid global urbanization and population growth, characterizing the concentrations and health effects of these aldehyde species is important as vehicular emissions are a major pollutant source in urban centers (Bauri et al, 2016; Crosbie et al, 2014; Hazrati et al, 2016b; Mannucci and Franchini, 2017; Masih et al, 2016; Morknoy et al, 2011; Rad et al, 2014; Sarkar et al, 2017; Saxena and Ghosh, 2012; Tunsaringkarn et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These two species have been targeted in numerous toxicological studies owing to their deleterious health effects (Health and Services, 1999; Neghab et al, 2017; Salthammer et al, 2010; Til et al, 1988; Tunsaringkarn et al, 2012b, 2012c). Their ubiquity and importance in ambient air have been documented in many past studies (Lü et al, 2016; Neghab et al, 2017; Sarkar et al, 2017). Owing to rapid global urbanization and population growth, characterizing the concentrations and health effects of these aldehyde species is important as vehicular emissions are a major pollutant source in urban centers (Bauri et al, 2016; Crosbie et al, 2014; Hazrati et al, 2016b; Mannucci and Franchini, 2017; Masih et al, 2016; Morknoy et al, 2011; Rad et al, 2014; Sarkar et al, 2017; Saxena and Ghosh, 2012; Tunsaringkarn et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…One of the main anthropogenic sources of air pollution in urban atmospheres is vehicular exhaust (Lü et al, 2010, 2016; Viskari et al, 2000), with a chief component being volatile organic compounds (VOCs) (Ho et al, 2016; Tunsaringkarn et al, 2012a). The main class of VOCs is aldehyde species, with the primary components being formaldehyde (HCHO, hereinafter FA) and acetaldehyde (CH 3 CHO, hereinafter AA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine particulate matter (FP), which differs from gas pollutants (Shy et al, 2015;Ho et al, 2016;Lü et al, 2016), is one of the most important hazardous pollutants (Lee et al, 2001;McGarry et al, 2011;Mullins et al, 2013;Stephens et al, 2013;Hussein et al, 2015;Lin et al, 2015;Mašková et al, 2016) as it is highly associated with public health concerns as toxic aerosol due to persistent lung damage (Matson, 2005;Gehin et al, 2008). Previous research has indicated that particles less than 0.5 µm in diameter might contribute the most to the adverse health effects of particulate air pollution and the risk of adverse health effects might increase with decreasing particle size (Meng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However limited for the odor emissions of carbonyls and phenols have been reported (Sims et al, 1993). Carbonyls are commonly detected in the indoor or outdoor air in the environment (Bernabe et al, 2015;Yao et al, 2015;Lü et al, 2016). Their concentrations can vary due to seasonal or diurnal effects, and source differences (Guo al., 2015;Leuchner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%